2015
DOI: 10.1111/epi.13004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long‐term quality of life after pediatric epilepsy surgery

Abstract: SUMMARYObjective: This study examined the influence of seizures, antiepileptic drugs (AEDs), intelligence quotient (IQ), and symptoms of depression and anxiety on health-related quality of life (HRQOL) 4-11 years after pediatric epilepsy surgery. Methods: Participants were 109 patients with childhood-onset intractable epilepsy; 71 had undergone surgery on average 6.9 years before this study. Patients and their parents completed questionnaires assessing HRQOL and internalizing behavior, a measure of depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 34 publications
(88 reference statements)
5
40
1
3
Order By: Relevance
“…The proportion of seizure‐free outcome amongst the surgical and pharmacological groups in our study was within the range reported in observational studies . We have included children with a variety of pathologies and different types of seizures (temporal vs extra‐temporal), which reflects the ‘real‐world’ phenomenon of pediatric epilepsy surgery that is often characterized by heterogeneous underlying etiology and seizure location.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The proportion of seizure‐free outcome amongst the surgical and pharmacological groups in our study was within the range reported in observational studies . We have included children with a variety of pathologies and different types of seizures (temporal vs extra‐temporal), which reflects the ‘real‐world’ phenomenon of pediatric epilepsy surgery that is often characterized by heterogeneous underlying etiology and seizure location.…”
Section: Discussionmentioning
confidence: 87%
“…Second, we did not consider other factors such as patient mood, caregiver factors, and family function that could potentially influence HRQoL after surgery. Patient mood, including depression and anxiety, was previously shown to be an important predictor of HRQoL after surgery . Family variables such as fewer family resources, caregiver mood, and caregiver unemployment were shown to be associated with diminished HRQoL in children with DRE .…”
Section: Discussionmentioning
confidence: 89%
“…A good seizure outcome appears to be associated with better behavioral outcome on parent‐reported measures, but this was considered in only four studies. Long‐term health‐related quality of life in children who have undergone epilepsy surgery has been shown to be associated with seizure freedom but also with presence of depression and anxiety symptoms . AEDs were not associated with changes in psychopathology.…”
Section: Discussionmentioning
confidence: 96%
“…The data were collected as part of a larger study examining multiple long‐term outcomes following epilepsy surgery in childhood, including quality of life (Puka & Smith, ) and emotional functioning (Tavares, Puka & Smith, ). The study was approved by the Research Ethics Board of the Hospital for Sick Children, and informed consent/assent was obtained from the patients and/or their parents.…”
Section: Methodsmentioning
confidence: 97%